A population‐based study of newly diagnosed epilepsy in infants. Issue 3 (17th December 2012) - Eltze, Christin M.; Chong, Wui K.; Cox, Tim; Whitney, Andrea; Cortina‐Borja, Mario; Chin, Richard F. M.; Scott, Rod C.; Cross, J. Helen
Summary Purpose: Most published data on infants presenting with epilepsy originate from hospital/specialist clinic settings and may therefore not be representative of the general population. We carried out a population‐based study to estimate the incidence of epilepsy onset in infants, to characterize the range of phenotypes and associated structural brain abnormalities, and to determine whether specific epilepsy diagnoses could be established at onset. Methods: Children between 1 and 24 months of age with new‐onset epilepsy were ascertained over 13 months from the residents in 15 boroughs of North London. Classification based on clinical information, electroencephalography (EEG), and neuroimaging data was undertaken independently by two pediatric neurologists. Neuroimages were reviewed by two neuroradiologists blinded to clinical details. Key Findings: A total of 57 children were enrolled giving an ascertainment‐adjusted incidence of 70.1 (95% CI [56.3, 88.5])/100, 000 children ≤2 years of age/year (ascertainment 76%). The incidence was highest among Asian children. An electroclinical syndrome was identified in 24 (42%) cases of which 21 were epileptic encephalopathies. Magnetic resonance (MR) images of 51 cases (89% of the total cohort) were reviewed. These demonstrated positive findings in 37 (72%) of 51 cases, of which 26 (51%) of 51 were etiologically relevant, and included developmental malformations in 11 (21%) of 51. Significance: In a population setting infantile onset epilepsy presents mostly with complex phenotypes commonly associated with structural brain abnormalities. Routine MR imaging at presentation is therefore justified. However, identification of specific electroclinical syndromes remains difficult at onset.